Agricultural monitoring system using esp32 microcontroller with IOT-Based LORA transmission - Achmad Zuchriadi; Fajar Rahayu; Silvia Anggraeni; Muhamad Alif Razi; Muchamad Oktaviandri; Irga Irga (Jurnal Mantik, 2023)
Smart farming is an agricultural management plan based on precise monitoring and calculation of agricultural parameters that are useful as a reference in taking appropriate actions. The application of Smart Farming is inseparable from the IoT system that supports processing and data collection. Remote large agricultural area, far from the public, limited access to electricity and difficult cellular network access. Responding to this, this research designed an IoT-based agricultural monitoring system by implementing the ESP 32 microcontroller and LoRa Transmission which uses solar panels as a power supply and is displayed via the Web Server Dashboard. Tests are carried out in the form of sensor readings, dashboard displays, and data transmission. The results obtained are that the agricultural monitoring system design works well with the sensors used to work and the ESP32 microcontroller to process data. LoRa and Internet data transmission can be sent properly indicated by synchronous data access. The monitoring dashboard can work properly as shown by the appropriate home page and graphic page.